How do Ontario family medicine residents perform on global health competencies? A multi-institutional survey - Veras, Mirella; Pottie, Kevin; Ramsay, Tim; Welch, Vivian; Tugwell, Peter (Revue canadienne de l’éducation médicale, 2013)
<!–[if gte mso 9]> <![endif]–> <!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin-top:0in; mso-para-margin-right:0in; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0in; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; –> <!–[endif] –> Background: There is an increased interest in global health among medical students, family medicine residents, and medical educators. This paper is based on research to assess confidence in knowledge and skills in global health in family medicine residents in five universities across Ontario. Methods: A web based survey was sent to 166 first-year family medicine residents from five universities within Ontario. Descriptive statistics were used to analyze residents’ confidence in their knowledge and skills in global health. The strength of association between each of the self-perceived knowledge and skills variables was assessed by the Spearman correlation coefficient. Results: The response rate ranged from 29% to 66% across the five universities. Self-perceived knowledge scores revealed that 34.3% of the respondents were very confident, 51.9% were somewhat confident, and 13.8% were not at all confident about their global health knowledge. Participants' confidence scores were lower in relation to knowledge of access to health care for low income nations (44.3%), and were better on their global health skills related to working in a team (70.9%) and listening actively to patients' concerns (64.6%). Conclusions: The global health competency scale has identified key areas of strengths and weaknesses of family medicine programs in global health education. This can be used to evaluate and analyze progress over time. <!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin-top:0in; mso-para-margin-right:0in; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0in; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; –> <!–[endif] –>